A new species of Bezzia Kieffer from Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Ronderos, María M.; Cazorla, Carla G. (Zootaxa, 2012)
Bezzia ventanensis Spinelli, a new Neotropical species, is described and illustrated based on pupae and adults. Pupae werecollected from muddy water from the edge of a stream margin in Sierra de la Ventana, Buenos Aires province, Argentina.Specimens were carried back to the laboratory and conditioned in vials until adult emergence. This new species is similarto Bezzia brevicornis (Kieffer), from which it can be mainly distinguished by the female adult bearing two well developed spermathecae, and by the pupal respiratory organ with 13–15 spiracles.